Remedy of Mixed Initiative Conflicts in Model-based System Engineering - Han, Fenglin; Herrmann, Peter (Electronic Communications of the EASST, 2012)
SPACE is a technique for model-driven engineering of reactive distributedsystems. One of the strengths of its tool-set Arctis is that the system engineercan formally analyze the models for design errors such that these can becorrected early in the development process. In this paper, we go a step further andintroduce a technique that refines the fault detection and, in addition, offers a highlyautomatic mechanism to remedy the errors. For that, we combine model checking,the already existing analysis method of Arctis, with graph transformation. Usinggraph rewriting rules, we can analyze the state space graph of a system for the exact reason of an error as well as remove the erroneous parts of a model by changing themodel description. We exemplify the approach by envisaging the detection and remedyof mixed initiatives, a quite common cause for faulty behavior in event-drivensystems that often is overlooked in system development.